If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 2x + -30 + -30 Reorder the terms: x = -30 + -30 + 2x Combine like terms: -30 + -30 = -60 x = -60 + 2x Solving x = -60 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. x + -2x = -60 + 2x + -2x Combine like terms: x + -2x = -1x -1x = -60 + 2x + -2x Combine like terms: 2x + -2x = 0 -1x = -60 + 0 -1x = -60 Divide each side by '-1'. x = 60 Simplifying x = 60
| x^2+4x+274=0 | | 5(w-7)=15+10w | | 25*(3-n)=25 | | -2=x/6-4 | | 129=2b-15 | | 2xsquared=162 | | 96000cm=km | | x^2-22x-271=0 | | 2x-9=-15+7x | | 6(z+3)-2z=2(2z+1) | | x12=x+1/15 | | -x^2-2x+3=2x-2 | | 15x=12x+1 | | 0.5=-4x^3+3x | | 2x+(-45)=-4 | | y=-4x^3+3x | | y=-4x^3-3x | | x+(x-1)=15 | | (y+z)p-(x+z)q=x-y | | 2x+-54=6 | | 3/7*2/9 | | x^2+2y^2+4=0 | | pq+30=6p+5q | | X^4+Y^4=Z^2 | | 3/10*X=12 | | 3x+.80=x+1.80 | | x+3=x*x | | 30093/(x)=185 | | p+q-pq=1 | | 6x^2-5x+171=0 | | 6x^2-5x+171= | | 30093/x=185 |